Ecofeminist Analysis of Environmental Economics - Karpenko, Kateryna; Karpenko, Ivan; Karpenko, Oksana (European Scientific Journal, ESJ, 2020)
The qualitatively new ecological situation is primarily a consequence of the consumer productive activity, which is based on confidence in the inexhaustible natural resources. But gender stereotypes that cause the interaction between nature and man, also greatly inhibit the solution of environmental and economic problems. In Western philosophy and economics, men’s activity in nature is identified with work and productive force, while women’s activity is manly recognized as natural and reproductive activity, subsumed into men’s production, and valued only individually and instrumentally. Contemporary environmental economics has to exclude this kind of identification. Acknowledging and valuing of women’s work and its absolute necessity should be discussed, like that of inputs from the natural environment, for the continuation of economic processes. We argue that an ecofeminist discourse improves the process of valuing in environmental economics. Ecofeminist analysis of environmental economics helps to overcome the bias of the dualistic methodology in this field of the economic theory.